Cataract following electric shock - Case report - Khadka, Simanta; Byanju, Raghunandan; Ranabhat, Sudha (Journal of Kathmandu Medical College, 2020)
Ocular trauma is the under-recognized cause of unilateral blindness particularly in developing nations.The growing demand on generated electricity has also led to increase in electricity related occupational trauma. We report a case of bilateral cataract in a 22 years professional electrician. He survived a high voltage electric shock and sustained burn injury on the right side of his head. Ocular examination revealed typical anterior as well as posterior subcapsular cataract in right eye and visually insignificant early anterior subcapsular vacuoles in the left eye. There was a significant difference in lenticular opacification density in between these two eyes. Uneventful phacoemulsification and foldable posterior chamber intraocular lens implantation was performed in the right eye and the sufferer was rehabilitated with normal best corrected visual acuity. The possibility of ocular complications and importance of ocular screening is emphasized in the survivors of electrical injury. The lenticular opacities can be successfully managed with surgery, however the final visual acuity depends on damage to other vital ocular structures. The clinical features, pathogenic mechanism of these opacities and review of the literatures are discussed.